Low frequency oscillations in U-2M conditioning RF discharges - Dreval, M.B.; Shapoval, A.M.; Beletskii, A.A.; Pavlichenko, R.O.; Ozherel’yev, F.I.; Makhov, M.M. (Вопросы атомной науки и техники, 2018)
MHD oscillations were studied in low magnetic field (B₀ = 0.01 T) radio frequency discharges of the URAGAN-2M (U-2M) stellarator. Coherent oscillations are observed by bolometers, triple Langmuir probe microwave interferometer (140 GHz) and magnetic pick-up coils in different toroidal cross-sections of U-2M. Modified diagnostics show, that the plasma beta (β = nT/(μ₀B² )) is rather high in these discharges in spite of the low temperature (Te = 10…50 eV) and density (ne = (0.5…1)∙10¹² cm⁻³ ) due to very low magnetic field. Variation of the magnetic configuration of U-2M substantially modifies fluctuations amplitude, oscillating modes type and frequency. Rotated m = 2 mode is transformed into the Sawtooth-like oscillations in different magnetic configurations. Strong dependence on the magnetic configuration indicates that observed in U-2M phenomena can have similar nature as in stellarator high temperature plasmas.